FAKTOR PENYEBAB RENDAHNYA PARTISIPASI PEMILIH DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI PELALAWAN DI KECAMATAN PANGKALAN KERINCI TAHUN 2015 - Fitri Wulan Sundari; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The regency is a division Kampar, which was established by Act No. 53 of 1999. Initially composed of four sub-district. Subdistrict Pangkalan Kerinci is the capital of Pelalawan. Basically the success of an election is determined by several things these include the voter, which is one characteristic of a democratic government that is a government based on community participation.The concept of the theory that researchers use is participation. said participation comes from the word to Participate, which can be interpreted to participate. According Tosun participation can create community, the various activities, both local and national scale. Participation means participation of a person or group of people in the development process in the form of a statement.This study uses qualitative research methods with an assessment of descriptive data. In collecting the data, researchers use interviewing techniques, observation and studikepustakaan. By using key informants and informant as a supplementary source of information.The results of this study indicate that factors affecting the low turnout in the election of the Regent and Vice Regent in the District of Pangkalan Kerinci Pelalawan are technical factors, employment, socialization, administrative factors and political factors.Keywords: Causes Low Voter Participation